Hybrid RANS-LES for turbomachinery - Jefferson-Loveday, Richard J. (2018)
A range of popular hybrid Reynolds averaged Navier-Stokes- large eddy simulation (RANS-LES) methods are tested for cavity and labyrinth seal flows using an in-house high order computational fluid dynamics (CFD) code and a commercial CFD code. The models include the Spalart-Allmaras (SA) and Menter SST variants of delayed detached eddy simulation (DDES), the Menter scale adaptive simulation (SAS) model, and a new enhanced variant of SA DDES recently presented in the literature. The latter modifies the original definition of the subgrid length-scale used in DDES based on local vorticity and strain. For both geometries, the meshes are hybrid RANS-LES adequate. Very low levels of resolved turbulent content are observed for both the cavity and labyrinth seal flows for all models apart from the enhanced version of DDES. Similar findings are observed for both the commercial and in-house CFD codes. For both cases most models essentially produce a quasi-two-dimensional flow field with minimal resolved content. For the cavity simulations there is a significant under prediction of turbulent statistics. The enhanced version of SA-DDES shows a significant improvement and resolves turbulent content over a wide range of scales. Improved agreement with experimental measurements is also observed. It is recommended that extreme care should be taken where hybrid RANS-LES simulations are essentially steady but have lower than RANS levels of eddy viscosity.